Morphological Studies: City Image and Urban Design Elements at Ngesrep Timur Corridor - Intan Muning Harjanti (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
Semarang as the capital of Central Java has an important role in the development of the city, especially in the Ngesrep Timur corridor which connecting UNDIP education area with other areas around it. The rapid development of UNDIP, followed by the development of Ngesrep Timur corridor. Therefore it is necessary to study morphology of urban image elements and urban design elements, in order to create a comfortable and pleasant atmosphere amid the density of the Ngesrep Timur corridor. This report used descriptive qualitatve approach, based on guiding theory of city image elements and urban design analysis.Analysis of city image elements resulted path form main roads and gangways settlement; edges form toll road, Setiabudi Road and settlement roads; district as a function of trade and services and settlement; nodes form the junction of Jl. Setiabudi to Jl. East Ngesrep; landmarks form Diponegoro Statue. Urban design analysis resulted dominant land used is trade and service and settlement, and form mass of building have enough good and interesting. The existence of circulation and parking is not sufficient;open space in this corridor form field and parking area, but the existence of green open space is not sufficient. Pedestrian ways are available, but its functioning is not maximal yet. Supporting activities in this corridor is commercial activities and preservation in this corridor have not been seen.